EFFECT OF ANDROGRAPHIS PANNICULATA ON IMMUNITY AND DUODENAL MORPHOLOGY OF PROGENY OF NICOBARI FOWL - T. Sujatha; J. Sunder; A. Kundu (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The research was carried out to study the inovo effect of Kalmegh herbal feed supplementation in Nicobari fowl on immunity and duodenal morphology of their progeny. At the age of 35 weeks, breeding fowls were assigned to three diets namely, T1 (Control), T2 – diet supplemented with 1 g Kalmegh powder per bird per day and T2 - 3 g of Kalmegh powder. Breeder fowls fed with 3 g and 1 g Kalmegh powder showed significantly higher HA titre against Goat RBC. The progeny of breeders fed with 3 g of kalmegh showed a significantly (P<0.05) higher HA titre at 12 and 16 weeks of age and lower crypt depth and higher villi height. It was concluded that 3 g of Kalmegh powder in the feed of breeder fowl could improve immunity and gut health of progeny.